Oil price shocks and U.S. dollar exchange rates. (1st October 2016) - Chen, Hongtao; Liu, Li; Wang, Yudong; Zhu, Yingming
Abstract: In this paper, we investigate the impacts of oil price shocks on the bilateral exchange rates of the U.S. dollar against currencies in 16 OECD countries. Our empirical findings indicate that the responses of dollar exchange rates to oil price shocks differ greatly depending on whether changes in oil prices are driven by supply or aggregate demand. Oil price shocks (need to say supply or demand shocks here) can explain about 10%–20% of long-term variations in exchange rates. The explanatory ability of oil shocks to exchange rate variations becomes much greater after global financial crisis. Based on parametric and nonparametric tests, we find little evidence of nonlinear relations between oil prices and exchange rates. Highlights: The effects of oil supply and shocks on exchange rates are heterogeneous. Oil shocks can explain about 20% of exchange rate variations. The effects of oil shocks become much stronger after financial crisis. The relationships between oil and exchange rates are not nonlinear.